Thrombolysis related symptomatic intracranial hemorrhage in estimated versus measured body weight. Issue 2 (February 2020) - Truc My Nguyen, T; van de Stadt, Stephanie IW; Groot, Adrien E; Wermer, Marieke JH; den Hertog, Heleen M; Droste, Hanneke M; van Zwet, Erik W; van Schaik, Sander M; Coutinho, Jonathan M; Kruyt, Nyika D
Background and aim: In acute ischemic stroke, under- or overestimation of body weight can lead to dosing errors of recombinant tissue plasminogen activator with consequent reduced efficacy or increased risk of hemorrhagic complications. Measurement of body weight is more accurate than estimation of body weight but potentially leads to longer door-to-needle times. Our aim was to assess if weight modality (estimation of body weight versus measurement of body weight) is associated with (i) symptomatic intracranial hemorrhage rate, (ii) clinical outcome, and (iii) door-to-needle times. Methods: Consecutive patients treated with intravenous thrombolysis between 2009 and 2016 from 14 hospitals were included. Baseline characteristics and outcome parameters were retrieved from medical records. We defined symptomatic intracranial hemorrhage according to the European Cooperative Acute Stroke Study (ECASS)-III definition and clinical outcome was assessed with the modified Rankin Scale. The association of weight modality and outcome parameters was estimated with regression analyses. Results: A total of 4801 patients were included. Five hospitals used measurement of body weight (n = 1753), six hospitals used estimation of body weight (n = 2325), and three hospitals (n = 723) changed from estimation of body weight to measurement of body weight during the study period. In 2048 of the patients (43%), measurement of body weight was used and in 2753 (57%), estimation of body weight. In the measurement of body weight group, an inbuilt weighing bed was used in 1094 patients (53%) and a patient lift scale in 954 patients (47%). In the estimation of body weight group, policy regarding estimation was similar. Estimation of body weight was not associated with increased symptomatic intracranial hemorrhage risk (adjusted odds ratio = 1.16; 95% confidence interval 0.83–1.62) or favorable outcome (adjusted odds ratio = 0.99; 95% confidence interval 0.82–1.21), but it was significantly associated with longer door-to-needle times compared to measurement of body weight using an inbuilt weighing bed (adjusted B = 3.57; 95% confidence interval 1.33–5.80) and shorter door-to-needle times compared to measurement of body weight using a patient lift scale (−3.96; 95% confidence interval −6.38 to −1.53). Conclusion: We did not find evidence that weight modality (estimation of body weight versus measurement of body weight) to determine recombinant tissue plasminogen activator dose in intravenous thrombolysis eligible patients is associated with symptomatic intracranial hemorrhage or clinical outcome. We did find that estimation of body weight leads to longer door-to-needle times compared to measurement of body weight using an inbuilt weighing bed and to shorter door-to-needle times compared to measurement of body weight using a patient lift scale.